PERBANDINGAN ALGORITMA DES, AES, IDEA, DAN BLOWFISH BERDASARKAN PANJANG KUNCI DAN CIPHERTEXT SEBAGAI INDIKATOR KEAMANAN DATA - Faqih Rifaldy; Hans Pran Limbong; Maulana Firjatullah; Rafli Arya Gading; M Irsan Prayoga; Ibnu Rusydi (Journal of Research and Publication Innovation, 2026)
The rapid growth of information technology has increased the need for secure data transmission, making cryptography a fundamental component of computer security systems. Symmetric cryptographic algorithms play an important role in protecting data confidentiality by transforming plaintext into ciphertext that is difficult to interpret by unauthorized parties. This study aims to compare the symmetric cryptographic algorithms DES, AES, IDEA, and Blowfish based on key length and ciphertext length as indicators of data security. The research utilizes a dataset consisting of 120,000 encryption records containing information on algorithm type, key length, and ciphertext length. The analysis is conducted using a descriptive comparative approach to evaluate differences in security characteristics among the algorithms. Key length is analyzed as an indicator of resistance to brute-force attacks, while ciphertext length is examined to assess encryption complexity and data transformation behavior. The results show that DES has the shortest key length and produces relatively less complex ciphertext, indicating lower security. IDEA demonstrates moderate security characteristics, while AES and Blowfish exhibit larger and more flexible key lengths along with more varied ciphertext patterns. These characteristics suggest that AES and Blowfish provide higher security compared to DES and IDEA. This study concludes that key length and ciphertext characteristics can be used as preliminary indicators in evaluating the relative security of symmetric cryptographic algorithms. However, this research does not include performance testing or cryptanalysis simulations, which can be explored in future studies.